Xenobiology for the Biocontainment of Synthetic Organisms: Opportunities and Challenges - Lucía Gómez-Tatay; José Miguel Hernández-Andreu (Life, 2024)
Since the development of recombinant DNA technologies, the need to establish biosafety and biosecurity measures to control genetically modified organisms has been clear. Auxotrophies, or conditional suicide switches, have been used as firewalls to avoid horizontal or vertical gene transfer, but their efficacy has important limitations. The use of xenobiological systems has been proposed as the ultimate biosafety tool to circumvent biosafety problems in genetically modified organisms. Xenobiology is a subfield of Synthetic Biology that aims to construct orthogonal biological systems based on alternative biochemistries. Establishing true orthogonality in cell-based or cell-free systems promises to improve and assure that we can progress in synthetic biology safely. Although a wide array of strategies for orthogonal genetic systems have been tested, the construction of a host harboring fully orthogonal genetic system, with all parts operating in an orchestrated, integrated, and controlled manner, still poses an extraordinary challenge for researchers. In this study, we have performed a thorough review of the current literature to present the main advances in the use of xenobiology as a strategy for biocontainment, expanding on the opportunities and challenges of this field of research.